Prototype Alat Pengukur Jarak Aman kendaraan Menggunakan Sensor Ultrasonik dan Layar LCD Berbasis Arduino Uno - Muhamad Hilmansyah Susanta (PT. Pustaka Cendekia Publisher, 2025)
Car head-on collisions, or accidents in which a vehicle hits the back of another vehicle, one of the causes is due to the lack of a safe distance. The distance that is too close to the vehicle in front makes the reaction time very short, making the collision difficult to avoid. Based on the problems above, a tool was created to monitor the safe distance between vehicles. So that the distance of the vehicle can be seen on the LCD screen. Some components include using ultrasonic sensors, Arduino Uno microcontrollers and 16 x 2 LCD screens. Ultrasonic sensors function as vehicle distance meters and LCD screens function to display the distance values ​​read by the ultrasonic sensor. Arduino Uno microcontrollers function as data processors both from ultrasonic sensors and to 16x2 LCD screens.